IMPROVE AUDIT REPORTING BY ANALYZING THE LIQUIDITY OF THE AUDITED ENTITY - S. Ponomareva (Вестник университета)
This article deals with the study of issues of improving the audit reporting by financial analysis of the audited entity in terms of changes in market trends in their development. The main features of the application of audit analytical procedures, illustrating their application by assessing liquidity has been defined. Focusing on the prospects of applying the international standard of audit 520 «Analytical procedures», in the framework of assessing the financial situation, the author determines that the organization’s audit planning system should be based on personal observations of the auditor, audit data of previous years, budget data, planning and actual calculations. The analytical procedures performed by the auditor during the audit, contribute to the formation of a General conclusion formed in the course of assessing the reliability of individual elements of the financial statements and identify the risk of material misstatement of the financial statements.